From the Revolution to the Maquiladoras : Gender, Labor, and Globalization in Nicaragua - Mendez, Jennifer Bickham (Book collections on Project MUSE., 2005)
Jennifer Bickham Mendez looks at how grassroots organisations tap into global networks and how gender plays into transnational political practices, addressing these issues through extended ethnographic research, centred on Nicaragua.